Giant Cell Arteritis: A Diagnostic Challenge in an Older Adult - Jorge Luiz de Carvalho Mello; Raul Sakuma Narita; Frederico Palumbo Araújo; Diba Maria Sebba Tosta de Souza; Vitor Angelo Carluccio Galhardo (Brazilian Society of Geriatrics and Gerontology, 2024)
Giant cell arteritis is a large-vessel vasculitis usually seen in older adults. The inflammatory process results in systemic, ophthalmic, and neurological lesions. It is difficult to diagnose in older adults and may present as a medical emergency. Here, we report the case of an 83-year-old woman who presented with bitemporal headache, jaw claudication, glossodynia, failure to thrive, and amaurosis fugax. The findings supported the hypothesis of giant cell arteritis. Despite receiving treatment, the patient died of an acute myocardial infarction. Headache in older adults raises the possibility of giant cell arteritis, especially when combined with an ophthalmic emergency. Many symptoms indicate the condition, but the diagnosis may be challenging, especially for the generalist physician.